Parts unknown : wrestling, gimmicks and other works - Holmes, Michael, 1966- (Insomniac Press, 2004)
Once again proving that no subject matter is beyond his poetic grasp, Michael Holmes now takes on the carnivalesque world of professional wrestling. With humour and bone-cracking language, Parts Unknown bridges the artificial trenches that established cultural endeavours have dug between themselves and their ''lowbrow'' athletic neighbours. These high-flying poems strut to their own music and enter the literary ring ready to rumble.